In Vivo Chemoselective Photoacoustic Imaging of Copper(II) in Plant and Animal Subjects. Issue 6 (15th January 2019) - Zeng, Leli; Ma, Gongcheng; Xu, Han; Mu, Jing; Li, Fan; Gao, Xiaoting; Deng, Zhuoting; Qu, Junle; Huang, Peng; Lin, Jing
Abstract: The detection of Cu 2+ in living plants and animals is of great importance for environment monitoring and disease diagnosis. Here, a near‐infrared (NIR) turn‐on photoacoustic (PA) probe (denoted as LET‐2) is developed for Cu 2+ detection in living subjects, such as soybean sprouts and mice. The absorbance band of LET‐2 shifts from 625 to 715 nm after the interaction with Cu 2+, thus producing strong PA signal output at 715 nm (PA715 ) as an indicator. The PA715 value is increased as a function of the concentration of Cu 2+ (0 × 10 −6 –20 × 10 −6 m ), with a calculated limit of detection of 10.8 × 10 −9 m . More importantly, both in vitro and in vivo studies in soybean sprouts and mice indicate that the as‐prepared LET‐2 PA probe is highly sensitive and selective for Cu 2+ detection. These findings provide a solution for in vivo detection of metal ions by using chemoselective PA probes. Abstract : A near‐infrared turn‐on photoacoustic probe (LET‐2) is developed for chemoselective photoacoustic imaging of copper(II) in plant and animal subjects.